Ethical boundaries and cybercultural dynamics in virtual drama education: Navigating student-educator interactions and role confusion - Azadeh Mehrpouyan (Social Sciences and Humanities Open, 2025)
This paper explores the interplay of ethics, CyberCulture, and artificial intelligence (AI) in virtual drama education. The present study critically assesses the ethical challenges and opportunities within digital learning environments, emphasizing AI's role in enhancing student engagement and ethical reasoning. Key issues examined include the necessity for critical thinking, respectful dialogue, and reliance on credible sources.The study proposes a CyberCulture framework to address ethical dilemmas and promote cultural awareness and adaptability within digital learning networks. Based on interview responses, 65 % of students indicated difficulty differentiating between appropriate communication styles in academic versus social online interactions. According to educator interviews, instances of uncivil discourse and misinformation decreased by 40 % following the implementation of a CyberCulture training module focused on ethical communication and information literacy.These results suggest that when guided by appropriate CyberCulture principles, AI-enhanced virtual drama environments can facilitate equitable quality education while mitigating uncivil discourse and misinformation through structured ethical communication protocols. Integrating AI systems in drama classes is presented as a means to foster ethical discourse in virtual settings.